2015
DOI: 10.4236/ojss.2015.511026
|View full text |Cite
|
Sign up to set email alerts
|

In-Season Side-Dressing of Urea and Ammonium Nitrate to Cotton on No-Till Soils with High Residual Nitrogen and Pre-Plant Nitrogen Application

Abstract: It is essential to develop innovative approaches that can apply N more efficiently. The objective of this study was to examine in-season side-dress urea and ammonium nitrate (UAN) applications to cotton on no-till soils with high residual N fertility. A field trial was conducted near Milan, TN in 2011 and 2012 with strip plots in a RCB design with three replicates. The following six in-season side-dress fluid UAN treatments were compared: 1) zero N; 2) low uniform-rate N application of 56 kg·N·ha −1 ; 3) high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Nitrogen fertilizer is often applied on the soil surface in no-tillage production systems without any mechanical incorporation into the soil in many areas around the world such as the State of Tennessee 1 . Ammonium nitrate (AN) can be surface broadcast since it has a low potential for N loss to the atmosphere via ammonia volatilization 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fertilizer is often applied on the soil surface in no-tillage production systems without any mechanical incorporation into the soil in many areas around the world such as the State of Tennessee 1 . Ammonium nitrate (AN) can be surface broadcast since it has a low potential for N loss to the atmosphere via ammonia volatilization 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Post‐harvest N content in soil profile is a vitally important indicator in environmental assessment. High levels of post‐harvest N in the soil profile have been increasingly observed in cotton and corn production systems in Tennessee and other states in recent years (Yin, 2015; Sharma and Bali, 2018). Bausch and Delgado (2005) found that in‐season N application according to ground‐based sensing technology significantly reduced residual NO 3 − –N level in the soil depth of 1.5 m. However, Yin (2015) noted that no significant effect on post‐harvest inorganic N (NO 3 − –N + NH 4 + –N) content in 60‐cm soil profile was observed under different in‐season N treatments.…”
Section: Disussionmentioning
confidence: 99%
“…High levels of post‐harvest N in the soil profile have been increasingly observed in cotton and corn production systems in Tennessee and other states in recent years (Yin, 2015; Sharma and Bali, 2018). Bausch and Delgado (2005) found that in‐season N application according to ground‐based sensing technology significantly reduced residual NO 3 − –N level in the soil depth of 1.5 m. However, Yin (2015) noted that no significant effect on post‐harvest inorganic N (NO 3 − –N + NH 4 + –N) content in 60‐cm soil profile was observed under different in‐season N treatments. Likewise, our results suggest that the use of in‐season sensor‐based VNMS do not significantly affect the post‐harvest residual N level in soil profile compared with FUNS, which might relate to the possibility that a larger amount of the applied N under FUNS was taken up by cotton plants, lost to deeper soil layers via nitrate leaching, and/or lost to the atmosphere via ammonium volatilization during the growing season and/or associated with the fact that the N application rates were reduced under VNMS relative to FUNS.…”
Section: Disussionmentioning
confidence: 99%